2017
DOI: 10.18203/2320-1770.ijrcog20174033
|View full text |Cite
|
Sign up to set email alerts
|

Methods of induction of labor in intrauterine fetal demise: a comparative study

Abstract: Background: This study was undertaken to evaluate and compare the efficacies of two different regimen for induction of labour in IUFD in an effort to find a better management of woman with IUFD. Methods: It was a hospital based prospective comparative study taken up in the Department of Obstetrics and Gynaecology, Assam Medical College and Hospital (AMCH), Dibrugarh for a period of 1 year. A total number of 90 cases were selected and randomly divided into 2 groups. The two groups were induced using regimen rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 2 publications
0
3
1
Order By: Relevance
“…Augmentation with oxytocin was required in 11.5% of women in group II, but no oxytocin was required within the combination group which was against our results. 13 Our results were not consonant with Maheshwari et al 15 who found that more cases required augmentation with oxytocin in group II than group I; however, the difference decided to be nonsignificant statistically.…”
Section: Resultscontrasting
confidence: 54%
See 1 more Smart Citation
“…Augmentation with oxytocin was required in 11.5% of women in group II, but no oxytocin was required within the combination group which was against our results. 13 Our results were not consonant with Maheshwari et al 15 who found that more cases required augmentation with oxytocin in group II than group I; however, the difference decided to be nonsignificant statistically.…”
Section: Resultscontrasting
confidence: 54%
“…13,14 The mean number of doses of misoprostol administered to women in the present study was less in the combination group in comparison with the misoprostol group and this finding is in harmony with the studies. [15][16][17] They concluded that pretreatment with mifepristone decreased the number of doses of misoprostol required for women to go into labor. We found a significant decrease in the requirement of misoprostol with prior use of mifepristone that is consistent with the literature that shows decreased prostaglandin requirement in cases where mifepristone was given and also owing to the effective cervical ripening by prior administration of mifepristone.…”
Section: Discussionmentioning
confidence: 99%
“…The difference was considered to be statistically significant with a p-value of 0.0096. In the study by Maheshwari S and Borgohain D, 6 the active phase from the onset of induction interval in group I was 13.42 ± 4.67 hours. In the study by Raghavan JV et al, 7 mean induction to active-phase interval with dinoprostone was 11.8 ± 5.855 hours.…”
Section: Discussionmentioning
confidence: 91%
“…In the misoprostol group, side symptoms like fever and shivering were more common than in the combined therapy group. [17,18]. According to Panda et al [19], the two groups did not differ significantly regarding complications suffered during labour and delivery.…”
Section: Discussionmentioning
confidence: 92%